Legal Consequences of a Sale and Purchase Deed Declared Void Due to an Unlawful Act (Decision Study Number: 2811 K/Pdt/2019) - Lumban Tobing, Ruth Yiska; Purba, Hasim; Siregar, Mahmul (LEGAL BRIEF, 2024)
This study examines the legal issues regarding the sale of collateral objects that are not bound by a deed of debt recognition, where in Decision No. 2811 K/Pdt/2019 there is a deed of sale and purchase issued as a guarantee of the return of rights. Through the normative legal research method, it was found that the sale of collateral objects based on a power of attorney to sell when the credit is in default is only valid if the debtor is proven to be in default and there is an agreement of the parties in accordance with Article 20 paragraphs (2) and (3) of the UUHT, while the power of attorney to sell made when the credit is binding is invalid because it is contrary to Law No. 4 of 1996 concerning Mortgage Rights and results in the cancellation of the power of attorney by law